2012
DOI: 10.1186/1471-2415-12-50
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of axial length, anterior chamber depth, lens thickness, and vitreous chamber depth in an adult population of Shahroud, Iran

Abstract: BackgroundOcular biometric parameters can be influenced by race, ethnicity, and genetics; their differences across different populations can probably explain differences in refractive errors in these populations. The aim of this study is to determine the normal range of axial length, anterior chamber depth, lens thickness, and vitreous chamber depth in the population of Shahroud in the north of Iran.MethodsIn the first phase of Shahroud Eye Cohort Study, the 40–64 year old population were sampled cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
79
9
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(129 citation statements)
references
References 32 publications
32
79
9
9
Order By: Relevance
“…Consistent with this trend, the mean spherical equivalent was more than þ0.45 diopters higher in the older subjects, in both men and women (Table 3, two-way ANOVA for sex and age, P < 0.001). Significant changes in axial length and corneal power with age have been previously reported in this sample 29,30 ; but as can be seen in Table 3, despite the differences in the prevalence of emmetropia and hyperopia, the axial length/corneal radius ratio (AL/CR) did not differ with age (two-way ANOVA for sex and age, P < 0.476).…”
Section: Resultssupporting
confidence: 46%
“…Consistent with this trend, the mean spherical equivalent was more than þ0.45 diopters higher in the older subjects, in both men and women (Table 3, two-way ANOVA for sex and age, P < 0.001). Significant changes in axial length and corneal power with age have been previously reported in this sample 29,30 ; but as can be seen in Table 3, despite the differences in the prevalence of emmetropia and hyperopia, the axial length/corneal radius ratio (AL/CR) did not differ with age (two-way ANOVA for sex and age, P < 0.476).…”
Section: Resultssupporting
confidence: 46%
“…Similar studies give a detailed description of these indices in different populations. [13][14][15][16][17][18][19][20][21][22][23][24] Results in our study showed that the mean CRF was 11.74 mm Hg and its normal range was from 8.19 to 15.28 mm Hg. The mean CH in this study was 11.49 mm Hg with a normal range from 7.67 to 15.31 mm Hg.…”
Section: Discussionmentioning
confidence: 93%
“…Biometric indices, especially AL, play a role in the difference between sexes. From previous studies, 23,24 we know that girls have a smaller AL than boys. Also, findings in some studies 9,25 suggest an inverse association between biomechanical properties and AL.…”
Section: Discussionmentioning
confidence: 96%
“…It has been proven that basic anatomical parameters (such as AL and ACD) in ophthalmology are variable in different countries according to ethnic groups, genetics and some environmental factors. In result, this may affect some parameters such as IOL power calculations, yet no study has specifically evaluated this matter (11, 12). Understanding region specific differences regarding IOL power calculations is vital for post cataract surgery evaluations.…”
Section: Introductionmentioning
confidence: 99%